RANCANG BANGUN SISTEM INFORMASI E-MARKETPLACE SEWA JASA KONTRAKTOR BERBASIS WEB (STUDI KASUS CIREBON KOTA DAN KABUPATEN) (Program Studi Teknik Informatika Universitas Muhammadiyah Cirebon, 2023)
Construction activities in the Cirebon city and regency area involve various processes and procedures carried out by contractors and clients. The contractor acts as the main manager of the construction providing various needs ranging from services to construction equipment. Building contractors are able to provide various types of building services, including the construction of houses, bridges, buildings, and many others. Cirebon city and regency Often service users in the region have difficulty finding contractors for the implementation of construction projects. This is due to lack of networking or contact with qualified and experienced building contractors. To facilitate the process of finding contractor services that suit the needs in the Cirebon city and regency areas, a contractor service rental E-Marketplace information system was designed that aims to make it easier for service users to find contractors in the Cirebon city and regency areas, which can be adjusted to the needs of the development project to be carried out. In the system designed includes contractor service rental activities, confirmation of proposals carried out by the contractor, determining the type of construction to be done, determining the area to be done, chatting between consumers and contractors. The system is built based on a website that uses PHP programming language, with interface development using the Laravel framework and its database using MySQL and the method used in system development is the SDLC system. The information system built is expected to be a reference and source of solutions to these problems.